Development of Learning by Doing Based on Experiential Learning to Improve The Strengthening of Social Care Attitudes Among SMP Al-Hidayah Sutam Students in Bandung Regency - Rizki Ramdani; Didik Sukriono; A. Rosyid Al Atok (Universitas Lambung Mangkurat, 2025)
The purpose of this research and development is to produce a Learning by Doing model based on Experiential Learning (LDEL) to increase the strengthening of students' social care attitudes. the product produced is in the form of a syntax model that can be used by teachers as a means to increase character education at school. the product is developed using the ADDIE model procedure which consists of analysis, design, develop, implement, and evaluate. The results showed that the feasibility of the product obtained from the model expert validation test reached 94% with very feasible criteria. while the practicality test was measured from the results of the students' response scores reaching 83% and the implementation of the syntax reaching 89%. During the implementation stage, the response of students reached 95.4%, the implementation of syntax reached 100%, and the response of the teacher reached a value of 97.7% with Very Practical criteria and the effectiveness test was measured through the recapitulation of the attitude journal, observation results, and student questionnaires which showed that this model not only improved attitudes in general, but also had a significant positive impact on individuals. It can be concluded that based on the series that has been carried out, the Experiential Learning-based Learning by Doing (LDEL) model is declared to meet the eligibility criteria to be used in the field as a character education model to increase the strengthening of students' empathy, cooperation and responsibility.